Refugee Stories: Constructing a Bosnian Girl’s Identity in Exile: A Case Study - Asikainen, Eija (Refuge: Canada’s Journal on Refugees, 1997)
The breakup of Yugoslavia turned into a violent civil war in Bosnia in the summer of 1991. The war did not begin as ethnic conflict, but ethnic traits were defined and collective memories were manipulated to mobilize people and to justify the violence between groups. In the case of Bosnian refugees, the questions concerning ethnicity and identity are especially important. The objective of this paper is to discuss the constitution ofthe refugee identity of an adolescent Bosnian girl in the context of exile. The research methods used were collection of refugee stories and participant observation. By collecting refugee stories, it is possible to examine the processes of identity constitution and the flexibility of identities.